MODERN METHODS OF DIAGNOSIS OF ANEMIAS IN NEWBORN (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
EV transfusion is one of the most frequent medical interventions in the neonatal period. The main purpose of transfusion is to maintain adequate oxygen delivery to tissues. It is an effective and rapid way to increase tissue oxygenation in newborns with blood loss [1,2,3].